Kondisi dan Strategi Nelayan Miskin dalam Memenuhi Kebutuhan Rumah Tangga di Kota Padang - Robi Mitra (Jurnal Community, 2022)
Study aims to describe the conditions of poor fishermen in Pasia Nan Tigo Village, Padang City and their strategies in meeting household needs. This study uses a narrative type qualitative method with purposive sampling and data analysis is descriptive. Data collection techniques through participatory observation, in-depth interviews and literature study. The results showed that: (1) Fishermen in Pasia Nan Tigo Village, Padang City, mostly live in simple houses that are rented annually and a small number already have their own houses with government assistance. (2) The economic condition of the fishermen is inadequate, sometimes the income obtained is not balanced with the expenditure in the household. (3) The educational condition of the fisherman's children is also concerning. Children of fishermen rarely continue their education to college, some even drop out of school when they are still in junior high or high school. This is caused by unaffordable costs and lack of motivation from parents. (4) Occupational health and safety as fishermen are adequate, although some of them still do not use work safety tools. (5) The strategies adopted by poor fishermen in meeting their household needs are opening savings, making loans to family or neighbors, and working side jobs.